Antecedents of student teachers' affective commitment to the teaching profession and turnover intention - Christophersen, Knut-Andreas; Elstad, Eyvind; Solhaug, Trond; Turmo, Are (European journal of teacher education, 2016)
Several European countries have experienced both a dearth of and reduction in the quality of applicants to teacher education study programmes. There is also significant leakage from these programmes. The rationale for this study therefore lies in the need to reduce teacher attrition. Research indicates that affective commitment to a profession is an important factor in sustaining good professional practice. This study explores the antecedents of both commitment and turnover intention among student teachers in Norway. The analysis indicates that there are stronger associations between commitment and experiences (particularly from dialogues with school mentors) gained during and after teaching practice in schools than is the case for the more campus-based elements of training. One implication is that there may be justification for placing emphasis on improving the preparation of school mentors and on points of contact between teacher educators and school mentors.